Sticky Knowledge: Barriers to Knowing in the FirmSticky Knowledge: Barriers to Knowing in the Firm, by SzulanskiGabriel. Thousand Oaks, CA: Sage, 2003. - Mahoney, Joseph T.; Williams, Charles (Academy of Management Review, 2003)
The article presents a review of the book ?Sticky Knowledge: Barriers to Knowing in the Firm,? by Gabriel Szulanski.